2013
DOI: 10.1038/srep02728
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of emergent patterns in plastic flows

Abstract: Crystalline solids undergo plastic deformation and subsequently flow when subjected to stresses beyond their elastic limit. In nature most crystalline solids exist in polycrystalline form. Simulating plastic flows in polycrystalline solids has wide ranging applications, from material processing to understanding intermittency of earthquake dynamics. Using phase field crystal (PFC) model we show that in sheared polycrystalline solids the atomic displacement field shows spatio-temporal heterogeneity spanning over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…1 corresponds to the local crystal orientation, θ , and the bottom panel represents the nearest neighbour characteristics, N coord , of each particle. A careful study shows that arrays of dislocations are mainly arranged along the grain boundaries with high misorientations, which is consistent with Frank condition, n  ∝ sin  dθ , where n is the line density along the grain boundary with the corresponding misorientaion dθ 2122.…”
Section: Resultssupporting
confidence: 71%
“…1 corresponds to the local crystal orientation, θ , and the bottom panel represents the nearest neighbour characteristics, N coord , of each particle. A careful study shows that arrays of dislocations are mainly arranged along the grain boundaries with high misorientations, which is consistent with Frank condition, n  ∝ sin  dθ , where n is the line density along the grain boundary with the corresponding misorientaion dθ 2122.…”
Section: Resultssupporting
confidence: 71%
“…One of the key question concerns the relationship between the rhe-ological behavior and the microscopic rearrangements that are ultimately responsible for the macroscopic mechanical behavior. While in crystalline solids it has been firmly established that yielding is mediated by defects, 4,5 identifying the microscopic elementary events leading to flow in amorphous materials is more challenging, due to the their disordered structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works focus on the irreversible (or plastic) rearrangements at the microscopic level [1][2][3][4][5][6][7], resulting from an applied deformation or stress, which are ultimately responsible for the macroscopic mechanical behavior. Research on amorphous solids is also relevant to crystalline materials [8]. On the one hand, simulations and experiments have revealed that particles in the grain boundaries (GBs) separating crystalline grains exhibit glassy dynamics [9,10].…”
Section: Introductionmentioning
confidence: 99%